Penegakan Kode Etik Terhadap Anggota Polri Yang Melakukan Penganiayaan Terhadap Sesama Anggota Polri (Studi Bidpropam Polda Maluku) - Andi Muhammad Taufik Rahadi; Sherly Adam; Michael Rolando Singkery (Universitas Muhammadiyah Mataram, 2026)
The enforcement of the Indonesian National Police (Polri) Code of Ethics plays a crucial role in maintaining the professionalism and integrity of the police institution, particularly in addressing violations committed by police officers. This study aims to analyze the mechanisms for handling and enforcing the Code of Ethics against police officers involved in assault cases at the Professional and Security Division (Bidpropam) of the Maluku Regional Police. This research employed an empirical legal approach using statutory and sociological perspectives. The study involved one key informant, the Head of the Internal Affairs Subdivision (Kasubbid Paminal) of Bidpropam Polda Maluku, selected through purposive sampling. Data were collected through interviews and document analysis and analyzed using a descriptive qualitative approach. The findings indicate that the enforcement process consists of report submission, preliminary investigation, and hearings before the Police Code of Ethics Commission (KKEP). Assault cases increased from 14 in 2022 to 16 in 2023 and 29 in 2024. Ethical proceedings were conducted concurrently with criminal justice processes through both internal disciplinary and general judicial mechanisms. The study concludes that, although the enforcement mechanism has been implemented procedurally, its preventive effectiveness requires strengthening through continuous supervision, guidance, and the internalization of professional ethical values.